Paper or Plastic? Data Equivalence in Paper and Electronic Diaries - Green, Amie S; Rafaeli, Eshkol; Bolger, Niall; Shrout, Patrick E; Reis, Harry T (Psychological methods, 2006)
Concern has been raised about the lack of participant compliance in diary studies that use paper-and-pencil as opposed to electronic formats. Three studies explored the magnitude of compliance problems and their effects on data quality. Study 1 used random signals to elicit diary reports and found close matches to self-reported completion times, matches that could not plausibly have been fabricated. Studies 2 and 3 examined the psychometric and statistical equivalence of data obtained with paper versus electronic formats. With minor exceptions, both methods yielded data that were equivalent psychometrically and in patterns of findings. These results serve to at least partially mollify concern about the validity of paper diary methods.